Erratum: A graphical tool for analysis and design of bi_characteristic_impedance transmission lines - D. Torrungrueng; P. Y. Chou; M. Krairiksh (My University, 2009)
Abstract Originally published in Microwave Opt Technol Lett 49: 2368–2372, 2007. © 2009 Wiley Periodicals, Inc. Microwave Opt Technol Lett 51: 1154, 2009; Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/mop.2426
Keywords: Microwave Engineering and Waveguides